Anti-reflection optical film and preparation method and application thereof

By introducing silica particles into the hardened coating of the antireflection film and forming active hydroxyl sites, combined with a specific coating formulation and photocuring process, the wear resistance, hardness and durability of the antireflection film are improved while maintaining a low reflectivity, which solves the problems of poor wear stability and high reflectivity of the antireflection film in the prior art.

CN119823638APending Publication Date: 2025-04-15NINGBO EXCITON TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411985624.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing anti-reflective films have problems with poor wear resistance and high reflectivity, and it is difficult to improve wear resistance, hardness and durability while reducing the reflectivity.

Method used

By introducing silica particles into the hardened coating and forming active hydroxyl sites under Plasma treatment, forming Si-O-Si chemical bonds with hollow silica microspheres in the antireflective coating, the adhesion force and strength of the hollow silica layer are enhanced. At the same time, the hardening and anti-reflective coating formulations, as well as the photocuring process, ensure excellent adhesion between the hardening and anti-reflective coatings.

Benefits of technology

The anti-reflective optical film has achieved a low reflectivity while taking into account better wear resistance, hardness and durability, and solves the problems of poor wear resistance and high reflectivity of the existing anti-reflective film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823638A_ABST
    Figure CN119823638A_ABST
Patent Text Reader

Abstract

The invention provides an anti-reflection optical film as well as a preparation method and application thereof, and relates to the technical field of anti-reflection films, in the anti-reflection optical film, a hardened coating is mainly prepared from the following components: a bifunctional polyurethane acrylate oligomer, a hexa-functional polyurethane acrylate oligomer, a photoinitiator, an antistatic agent and silicon dioxide particles; the anti-reflection coating is mainly prepared from the following components: a bifunctional polyurethane acrylate oligomer, a tetrafunctional polyurethane acrylate oligomer, a hexa-functional polyurethane acrylate oligomer, trimethylolpropane triacrylate, fluorine modified resin, a hollow silicon dioxide microsphere dispersion liquid, a photoinitiator, an antifouling auxiliary agent and a flatting agent. The technical problems that an existing anti-reflection film is poor in wear-resistant stability and high in reflectivity are solved, and the technical effects that the anti-reflection film has the low reflectivity and meanwhile has the good wear-resistant performance, hardness and durability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-reflection films, and in particular to an anti-reflection optical film and a preparation method and application thereof. Background Art

[0002] When using portable display devices in indoor and outdoor environments, due to strong natural light, the display screen often reflects the color and clarity of the displayed content. In order to improve the visibility of display devices, there are usually two strategies: one is to increase the brightness of the screen, and the other is to reduce the reflection of the screen. However, increasing the brightness will consume more power, which may further shorten the already limited standby time of smart devices. Therefore, more and more display device manufacturers choose to apply anti-reflection film (AR film) on the screen surface to reduce light reflection when used indoors and outdoors, effectively solving the visibility problem caused by reflected light.

[0003] The production process of anti-reflection film involves coating the surface of optical substrates with good transparency (PET (polyethylene terephthalate), SRF (super phase retardation film), TAC (triacetate) and PMMA (polymethyl methacrylate)) with thin films made of alternating stacks of materials with different refractive indices. When light passes through the interface of these materials, different optical path differences will be generated due to the differences in refractive index and film thickness. Through the carefully designed film structure and materials, the optical path differences of reflected light from different media can be interfered with each other, thereby effectively reducing the reflected light and achieving the anti-reflection effect. There are two main processes for preparing anti-reflection film: one is wet coating, including multi-layer superposition of hard coating, high refractive index coating and low refractive index coating; the other is to first wet-coat a hard coating, then use dry sputtering technology to superimpose multiple layers of high and low refractive index coatings, and finally wet-coat an anti-fingerprint layer. Wet coating technology, which takes into account both cost-effectiveness and efficiency, is gradually replacing dry sputtering technology, which has high equipment cost, high production cost and low efficiency, and has become the mainstream preparation method.

[0004] The main components of wet-coated anti-reflective coatings include fluorine-modified acrylate polymers or oligomers with a low refractive index and hollow microspheres (silicon dioxide, titanium dioxide, etc.). In particular, the surface of silica microspheres contains a certain number of active hydroxyl sites, which can be further modified and functionalized, and are therefore widely used in the design of anti-reflective coatings. In order to meet the conditions of optical destructive interference, the thickness of the anti-reflective coating designed for anti-reflective films is generally 90nm-120nm, and the coating also contains a layer of hollow silica microspheres, so the wear resistance of these coatings is generally not ideal.

[0005] Prior art CN 115561843 A discloses the introduction of fluorosilane-modified secondary nanoparticles into a coating formula. By adjusting the particle size of the secondary nanoparticles to be larger than the coating thickness, micro-protrusions can be formed on the coating surface to avoid direct friction on the coating, thereby improving the wear resistance of the anti-reflective coating. However, when the amount of secondary particles added is too much or the uniformity is poor, it is easy to cause an increase in the haze of the coating, and even lead to an over-standard situation. At the same time, when the hollow silica microspheres and the secondary nanoparticles are unevenly distributed, it is easy to cause the wear resistance to fluctuate.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] One of the purposes of the present invention is to provide an anti-reflective optical film with lower reflectivity while taking into account better wear resistance, hardness and durability, thereby solving the technical problems of poor wear resistance stability and high reflectivity of existing anti-reflective films.

[0008] The second object of the present invention is to provide a method for preparing an anti-reflective optical film, which has a simple and efficient process, is beneficial to reducing the reflectivity of the anti-reflective film, and is also beneficial to improving the wear resistance, hardness and durability, has a high success rate, and is suitable for industrial production.

[0009] A third object of the present invention is to provide an application of an anti-reflective optical film, which is beneficial to improving the visibility of a display device.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] In a first aspect, an anti-reflection optical film includes a hardening coating layer and an anti-reflection coating layer stacked on the hardening coating layer;

[0012] The hardened coating is formed by a hardening coating liquid, and the hardening coating liquid includes the following components:

[0013] Difunctional polyurethane acrylate oligomer, hexafunctional polyurethane acrylate oligomer, photoinitiator, antistatic agent and silicon dioxide particles;

[0014] The anti-reflective coating is formed by an anti-reflective coating liquid, and the anti-reflective coating liquid includes the following components:

[0015] Difunctional polyurethane acrylate oligomer, tetrafunctional polyurethane acrylate oligomer, hexafunctional polyurethane acrylate oligomer, trimethylolpropane triacrylate, fluorine-modified resin, hollow silica microsphere dispersion, photoinitiator, antifouling agent and leveling agent.

[0016] Furthermore, the hardened coating is laminated on the transparent substrate;

[0017] Preferably, the transparent substrate comprises at least one of PET, SRF, TAC and PMMA;

[0018] Preferably, the thickness of the transparent substrate is not less than 40 um;

[0019] Preferably, the thickness of the hardened coating is 3um-4um;

[0020] Preferably, the anti-reflection coating has a thickness of 100 nm-120 nm.

[0021] Further, the silicon dioxide particles include solid silicon dioxide particles;

[0022] Preferably, the silica particles are random silica particles;

[0023] Preferably, the particle size of the silica particles is 0.1um-0.2um;

[0024] Preferably, the silica particles are silica particles with hydrophobic surface treatment.

[0025] Further, the antistatic agent includes an ionic antistatic agent;

[0026] Preferably, the ionic antistatic agent is an anionic antistatic agent;

[0027] Preferably, the anionic antistatic agent includes at least one of alkyl sulfonates, alkyl sulfates, alkyl phosphates and alkylphenol polyoxyethylene ether sulfates;

[0028] Preferably, the anionic antistatic agent is bis(trifluoromethylsulfonyl)imide salt.

[0029] Further, the hollow silica microsphere dispersion includes at least one of a hollow silica microsphere dispersion treated with vinyl groups on the surface and a hollow silica microsphere dispersion treated with methacrylic acid groups on the surface;

[0030] Preferably, the surface of the hollow silica microsphere has at least 2 vinyl reaction sites;

[0031] Preferably, the particle size of the hollow silica microspheres is 30nm-100nm;

[0032] Preferably, the wall thickness of the hollow silica microspheres is 5nm-6.5nm;

[0033] Preferably, the porosity of the hollow silica microspheres is 40%-60%.

[0034] In a second aspect, a method for preparing the anti-reflective optical film according to any one of the above items comprises the following steps:

[0035] A hardening coating liquid is firstly coated on the surface of a transparent substrate and cured to form a hardened coating layer, and then an anti-reflection coating liquid is coated on the surface of the hardened coating layer and cured to form an anti-reflection coating layer, thereby obtaining the anti-reflection optical film.

[0036] Furthermore, the hardened coating layer is subjected to a solvent volatilization step before curing;

[0037] Preferably, the cumulative UV energy irradiated to the hardened coating during the curing process is 100 mJ / cm 2 -250mJ / cm 2 ;

[0038] Preferably, the hard coating has unreacted active vinyl sites after curing.

[0039] Furthermore, the hardened coating is subjected to a plasma treatment step after being cured, so that active hydroxyl sites are formed on the surfaces of the silicon dioxide particles floated onto the hardened coating under the plasma treatment.

[0040] Furthermore, the anti-reflective coating is subjected to a solvent volatilization step before curing;

[0041] Preferably, the oxygen concentration of the anti-reflective coating during curing is less than 200 ppm, and the cumulative UV energy irradiated is 500 mJ / cm 2 -1000mJ / cm 2 .

[0042] A third aspect provides an application of the anti-reflective optical film described in any one of the above items in a portable display device.

[0043] Compared with the prior art, the present invention has at least the following beneficial effects:

[0044] The anti-reflection optical film provided by the present invention introduces silica particles into the hardening coating layer, and the surface of the silica particles floating to the upper layer of the hardening coating layer can form active hydroxyl sites under plasma treatment, and can form Si-O-Si chemical bonds with hollow silica microspheres in the anti-reflection coating layer, thereby improving the adhesion and strength of the hollow silica layer; at the same time, the present invention designs the hardening coating liquid formula, the anti-reflection coating liquid formula and the light curing process, so that the hardening coating layer is not fully cured during the coating process, and a certain proportion of vinyl is retained as the remaining active sites that can be photocured. When the anti-reflection coating layer is subjected to the curing process, With sufficient UV energy, the remaining active sites in the hardening coating will be fully cross-linked with the anti-reflective coating, so that the two layers have excellent adhesion, providing a better bearing effect for the anti-reflective coating; in addition, the floating silica particles can appropriately increase the surface roughness of the hardening coating, and further enhance the adhesion between the hardening coating and the anti-reflective coating; in short, with the coordinated cooperation of the hardening coating liquid formula, the anti-reflective coating liquid formula and the specific process, the anti-reflective optical film of the present invention has lower reflectivity while also taking into account the characteristics of better wear resistance, hardness and durability, thereby solving the technical problems of poor wear resistance stability and high reflectivity of the existing anti-reflective films.

[0045] The method for preparing the anti-reflection optical film provided by the present invention has a simple process and high efficiency, is beneficial to reducing the reflectivity of the anti-reflection film, and is also beneficial to improving the wear resistance, hardness and durability, has a high success rate, and is suitable for industrial production.

[0046] The application of the anti-reflection optical film provided by the present invention is beneficial to improving the visibility of the display device. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 A schematic diagram of the structure of an anti-reflection optical film provided in one embodiment of the present invention;

[0049] Figure 2 A flow chart for preparing an anti-reflective optical film provided for one embodiment of the present invention.

[0050] Icons: 01-transparent substrate; 02-hardening coating; 03-anti-reflective coating; 04-hollow silica microspheres; 05-silica particles. DETAILED DESCRIPTION

[0051] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] According to a first aspect of the present invention, there is provided an anti-reflection optical film, comprising a hard coating layer and an anti-reflection coating layer stacked on the hard coating layer;

[0053] The hardened coating is formed by a hardened coating liquid, and the hardened coating liquid includes the following components:

[0054] Difunctional polyurethane acrylate oligomer, hexafunctional polyurethane acrylate oligomer, photoinitiator, antistatic agent and silicon dioxide particles;

[0055] The anti-reflective coating is formed by an anti-reflective coating liquid, and the anti-reflective coating liquid includes the following components:

[0056] Difunctional polyurethane acrylate oligomer, tetrafunctional polyurethane acrylate oligomer, hexafunctional polyurethane acrylate oligomer, trimethylolpropane triacrylate (TMPTA), fluorine-modified resin, hollow silica microsphere dispersion, photoinitiator, antifouling agent and leveling agent.

[0057] By introducing silica particles into the hardening coating, the surface of the silica particles that float to the upper layer of the hardening coating can form active hydroxyl sites under plasma treatment, which can form Si-O-Si chemical bonds with the hollow silica microspheres in the anti-reflective coating, thereby improving the adhesion and strength of the hollow silica layer; at the same time, through the design of the hardening coating liquid formula, the anti-reflective coating liquid formula and the photocuring process, the hardening coating is not fully cured during the coating process, and a certain proportion of vinyl is retained as the remaining active sites that can be photocured. When the anti-reflective coating is undergoing the curing process, the remaining active sites in the hardening coating will be fully cross-linked with the anti-reflective coating through sufficient UV energy, so that the two layers have excellent adhesion, providing a better bearing effect for the anti-reflective coating; in addition, the floating silica particles can appropriately increase the surface roughness of the hardening coating, further improving the adhesion between the hardening coating and the anti-reflective coating.

[0058] In summary, with the coordinated cooperation of the hardening coating liquid formula, the anti-reflective coating liquid formula and the specific process, the anti-reflective optical film of the present invention has lower reflectivity while also taking into account the characteristics of better wear resistance, hardness and durability, thus solving the technical problems of poor wear resistance stability and high reflectivity of existing anti-reflective films.

[0059] In the present invention, the hardening coating is laminated on the transparent substrate; wherein the transparent substrate includes but is not limited to at least one of PET, SRF, TAC and PMMA.

[0060] In a preferred embodiment, the thickness of the transparent substrate may be no less than 40 um, which is helpful to avoid obvious thermal deformation during baking, thereby avoiding uneven coating.

[0061] A typical structure of an anti-reflective optical film, see Figure 1 , from bottom to top, it includes a transparent substrate 01, a hardening coating 02 and an anti-reflection coating 03 stacked in layers;

[0062] The silicon dioxide particles 05 float to the upper layer of the hardening coating 02 and form Si—O—Si chemical bonds with the hollow silicon dioxide microspheres 04 in the anti-reflection coating 03 .

[0063] In the present invention, the thickness of the hardened coating can be 3um-4um, for example, 3um, 3.5um, 4um, but not limited thereto; the thickness of the anti-reflective coating can be 100nm-120nm, for example, 100nm, 105nm, 110nm, 115nm, 120nm, but not limited thereto.

[0064] In a preferred embodiment, the silica particles used in the hardening coating may be solid silica particles, and may further preferably be random silica particles; the particle size of the silica particles may be between 0.1um and 0.2um, and typical but non-limiting particle sizes are, for example, 0.1um, 0.12um, 0.14um, 0.16um, 0.18um, and 0.2um.

[0065] In a preferred embodiment, the silica particles need to be subjected to a hydrophobic surface treatment. After the hydrophobic surface treatment, when the solvent evaporates, it will spontaneously migrate to the coating surface due to the influence of surface tension. It can be further preferably a silane with a long-chain alkane group, for example, it can be at least one of dodecyltrimethoxysilane, hexadecyltrimethoxysilane and octadecyltrimethoxysilane.

[0066] In the present invention, the antistatic agent may be an ionic antistatic agent, and the ionic antistatic agent may preferably be an anionic antistatic agent, for example, it may be at least one of alkyl sulfonates, alkyl sulfates, alkyl phosphates and alkylphenol polyoxyethylene ether sulfates, and may further preferably be bistrifluoromethylsulfonyl imide salt.

[0067] It should be noted that in order to make the hardened coating liquid meet the appropriate viscosity range and solid content for coating, it is necessary to add an appropriate amount of solvent to dilute the coating liquid. The solvent can be at least one of propylene glycol methyl ether (PM), isopropyl alcohol (IPA), methyl isobutyl ketone (MIBK), butanone (MEK) and ethyl acetate (EA), and in particular, PM and / or MIBK can be preferred.

[0068] In a preferred embodiment, the hollow silica microspheres used in the anti-reflective coating need to be surface modified and modified. For example, a dispersion of hollow silica microspheres treated with a vinyl surface, a dispersion of hollow silica microspheres treated with a methacrylic group, a dispersion of hollow silica microspheres treated with a methyltrimethoxysilane surface, a dispersion of hollow silica microspheres with an amino surface treatment agent, and a dispersion of aminoethylaminopropyltrimethoxysilane can be selected. A dispersion of hollow silica microspheres treated with a vinyl or methacrylic group can be further preferred. The silane coupling agent containing a vinyl or methacrylic group used for treatment includes at least one of vinyltrimethoxysilane, vinylethoxysilane, vinyl-tri(2-methoxyethoxy)silane, and vinylmethyldimethoxysilane. In particular, considering the subsequent chemical bonding with the oligomer or acrylate monomer in the coating, it is preferred to use vinylethoxysilane with relatively low steric hindrance.

[0069] In the present invention, the solvent used to disperse the hollow silica microspheres may preferably be at least one of propylene glycol methyl ether (PM), isopropyl alcohol (IPA), methyl isobutyl ketone (MIBK), butanone (MEK) and ethyl acetate (EA), and in particular may preferably be PM and / or MIBK.

[0070] In a preferred embodiment, the surface of the hollow silica microspheres has at least two vinyl reaction sites, which can ensure that a network structure with a certain degree of crosslinking is further formed with adjacent silica microspheres or acrylate monomers and oligomers in the resin, which is beneficial to further improve the strength of the coating.

[0071] In a preferred embodiment, the particle size of the hollow silica microspheres can be between 30nm-100nm, and its typical but non-limiting particle size is, for example, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, and 100nm; the wall thickness of the hollow silica microspheres can be between 5nm and 6.5nm, and its typical but non-limiting wall thickness is, for example, 5nm, 5.5nm, 6nm, and 6.5nm.

[0072] In a preferred embodiment, the porosity of the hollow silica microspheres may be between 40% and 60%, and typical but non-limiting porosities are, for example, 40%, 45%, 50%, 55%, and 60%.

[0073] According to a second aspect of the present invention, there is provided a method for preparing the anti-reflection optical film as described in any one of the above, comprising the following steps:

[0074] A hardening coating liquid is first coated on the surface of a transparent substrate and cured to form a hardened coating layer, and then an anti-reflection coating liquid is coated on the surface of the hardened coating layer and cured to form an anti-reflection coating layer, thereby obtaining an anti-reflection optical film.

[0075] The method for preparing the anti-reflection optical film provided by the present invention has a simple process and high efficiency, is beneficial to reducing the reflectivity of the anti-reflection film, and is also beneficial to improving the wear resistance, hardness and durability, has a high success rate, and is suitable for industrial production.

[0076] In the present invention, the hardened coating layer is further subjected to a solvent volatilization step before being cured.

[0077] In a preferred embodiment, the cumulative UV energy irradiated to the hardened coating during the curing process can be 100 mJ / cm 2 -250mJ / cm 2 , which ensures that the hardened coating still has unreacted active vinyl sites after curing.

[0078] It should be noted that the hardening coating is not fully cured, but a certain proportion of vinyl is retained as the remaining active sites that can undergo photocuring. When the anti-reflective coating is cured, the light intensity and line speed of the UV light source are adjusted to obtain sufficient UV energy, and then the remaining active sites in the hardening coating will be fully cross-linked with the anti-reflective coating, and the two layers have good adhesion. The hardening coating provides a better bearing effect for the anti-reflective coating.

[0079] In a preferred embodiment, the hardened coating is further subjected to a plasma treatment step after curing, so that the surfaces of the silica particles that float onto the hardened coating form active hydroxyl sites under the plasma treatment, which is beneficial to form Si-O-Si chemical bonds with the hollow silica microspheres in the anti-reflective coating, thereby effectively improving the adhesion and strength of the hollow silica layer.

[0080] In the present invention, the anti-reflective coating is further subjected to a solvent volatilization step before being cured.

[0081] In a preferred embodiment, the oxygen concentration of the anti-reflective coating during the curing process can be lower than 200 ppm, and the cumulative UV energy irradiated can be 500 mJ / cm 2 -1000mJ / cm2 .

[0082] A typical method for preparing an anti-reflective optical film is shown in Figure 2 , including the following steps:

[0083] (1) adding each component and solvent according to the formula, stirring and mixing them thoroughly to obtain a hardening liquid, i.e., a hardening coating liquid;

[0084] Adding various components and solvents according to the formula, stirring and mixing them thoroughly, and obtaining a low refractive index liquid, i.e., an anti-reflective coating liquid;

[0085] (2) Based on the solid content of the obtained hardening solution, an OSP wire rod with a suitable mesh size is selected to evenly coat a layer of the hardening solution on the transparent substrate;

[0086] (3) placing the sample obtained by coating in step (2) in an oven at 80° C. to 100° C. and baking for 2 to 3 minutes to fully evaporate the solvent, thereby obtaining a hardened coating layer with a thickness of 3 μm to 4 μm;

[0087] (4) Adjust the light intensity and line speed of the tunnel UV equipment so that the cumulative UV energy irradiated to the hardened coating is 100mJ / cm 2 -250mJ / cm 2 Within the range, it is ensured that the hardened coating after UV curing still has a certain number of unreacted active vinyl sites to obtain a semi-finished product;

[0088] (5) placing the semi-finished product prepared in step (4) on a platform, and further subjecting the hardened coating to plasma treatment to activate the surface;

[0089] (6) Select an OSP wire rod with a suitable mesh number to evenly coat the low refractive index liquid on the surface of the hardened coating;

[0090] (7) baking the sample obtained by coating in step (6) in an oven at 80° C. to 100° C. for 2 to 3 minutes to fully evaporate the solvent, thereby obtaining an anti-reflection coating with a thickness of 100 nm to 120 nm;

[0091] (8) The sample obtained in step (7) is placed in a transparent glass box, and the inert gas (nitrogen) is replaced therein to control the oxygen concentration in the box to be less than 200 ppm. The sample is then placed in a tunnel-type UV curing device for photocuring reaction, and the light source intensity and line speed are adjusted to ensure that the cumulative UV energy irradiated to the anti-reflective coating is 500 mJ / cm 2 -1000mJ / cm 2 , and obtain the finished anti-reflection optical film.

[0092] According to a third aspect of the present invention, there is provided a use of any of the above-mentioned anti-reflection optical films in a portable display device.

[0093] The application of the anti-reflection optical film provided by the present invention is beneficial to improving the visibility of the display device.

[0094] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0095] The composition of the hardening coating liquid 1 is shown in Table 1. 28% by mass of a difunctional polyurethane acrylate oligomer, 12% by mass of a hexafunctional polyurethane acrylate oligomer, 0.2% by mass of a photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.75% by mass of a 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 0.15% by mass of an antistatic agent are weighed in sequence as the main part of the hardening coating liquid, and 58.75% by mass of MIBK is added thereto for dilution; 1% by mass of surface-treated silica particles with a particle size of about 0.1-0.2 um is added to the above main resin, and the mixture is fully stirred to obtain a hardening coating liquid 1 with a solid content of about 50%;

[0096] The composition of the hardening coating liquid 2 is shown in Table 1. 28% by mass of a difunctional polyurethane acrylate oligomer, 12% by mass of a hexafunctional polyurethane acrylate oligomer, 0.2% by mass of a photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.75% by mass of a 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 0.15% by mass of an antistatic agent are weighed in sequence as the main part of the hardening coating liquid. 58.75% by mass of MIBK is then added thereto for dilution. The mixture is stirred thoroughly to obtain a hardening coating liquid 2 having a solid content of about 50%.

[0097] The composition of the hardening coating liquid 3 is shown in Table 1. 28% by mass of a difunctional polyurethane acrylate oligomer, 12% by mass of a hexafunctional polyurethane acrylate oligomer, 0.2% by mass of a photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.75% by mass of a 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 0.15% by mass of an antistatic agent are weighed in sequence as the main part of the hardening coating liquid, and 58.75% by mass of MIBK is added thereto for dilution; 5% by mass of surface-treated silica particles with a particle size of about 0.1-0.2 um are added to the above main resin, and the mixture is fully stirred to obtain a hardening coating liquid 3 with a solid content of about 50%;

[0098] The composition of the hardening coating liquid 4 is shown in Table 1. 28% by mass of a difunctional polyurethane acrylate oligomer, 12% by mass of a hexafunctional polyurethane acrylate oligomer, 0.2% by mass of a photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.75% by mass of a 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 0.15% by mass of an antistatic agent are weighed in sequence as the main part of the hardening coating liquid, and then 58.75% by mass of MIBK is added thereto for dilution; 1% by mass of surface-treated silica particles with a particle size of about 0.25-0.35 um is added to the above main resin, and the mixture is fully stirred to obtain a hardening coating liquid 4 with a solid content of about 50%;

[0099] The composition of the hardening coating liquid 5 is shown in Table 1. 28% by mass of a difunctional polyurethane acrylate oligomer, 12% by mass of a hexafunctional polyurethane acrylate oligomer, 0.2% by mass of a photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.75% by mass of a 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 0.15% by mass of an antistatic agent are weighed in sequence as the main part of the hardening coating liquid, and then 58.75% by mass of MIBK is added thereto for dilution; 1% by mass of silicon dioxide particles with a particle size of about 0.1-0.2 um and not subjected to surface treatment is added to the above main resin, and the mixture is fully stirred to obtain a hardening coating liquid 5 with a solid content of about 50%.

[0100] Table 1 Composition of hardening coating liquid 1-5

[0101]

[0102] The preparation process of the anti-reflective coating liquid is to weigh the corresponding mass fractions of difunctional polyurethane acrylate oligomer, tetrafunctional polyurethane acrylate oligomer, hexafunctional polyurethane acrylate oligomer, acrylate monomer, fluorine-modified oligomer, hollow silica microspheres, antifouling additive and leveling agent in sequence as the main resin, then add the corresponding mass fraction of solvent to the main resin, and obtain the anti-reflective coating liquid after sufficient stirring.

[0103] The compositions of anti-reflective coating solutions 1-16 are shown in Table 2, Table 3 and Table 4, respectively.

[0104] Table 2 Composition of antireflective coating liquid 1-6

[0105]

[0106] Table 3 Composition of antireflective coating liquid 7-12

[0107]

[0108] Table 4 Composition of antireflective coating liquids 13-16

[0109]

[0110] Examples 1-7

[0111] Embodiment 1-7 provides an anti-reflection optical film, which is prepared by the following method:

[0112] (a) A PMMA substrate cut into A4 size and 40 μm thick was laid flat on a marble platform and further fixed at the front end with masking tape. Then, a hardening coating liquid was added to the front end of the substrate and a RDS7# wire rod was used to scrape the substrate at a uniform speed. After removing the excess glue liquid, the substrate was placed in an oven for baking to remove the solvent.

[0113] (b) After removing the solvent, the sample was subjected to a cumulative UV energy of 100-250 mJ / cm 2 Performing photocuring to obtain a semi-finished anti-reflective optical film coated with a hardened coating;

[0114] (c) Plasma treatment of the semi-finished product obtained above to obtain an anti-reflection optical film semi-finished product coated with a hardened coating and having improved surface activity;

[0115] (d) Add the anti-reflective coating liquid to the hardened coating, apply the anti-reflective coating using the RDS3# wire rod according to the above coating steps, and then place it in a glass box with an oxygen concentration of less than about 200 ppm, using a cumulative energy of about 500-1000 mJ / cm 2 Performing photocuring to obtain an anti-reflective optical film;

[0116] The specific composition of the anti-reflection optical films obtained in Examples 1-7 and the performance evaluation results are shown in Table 5.

[0117] Comparative Examples 1-4

[0118] Compared with Example 1, hardening coating solutions with different particle sizes, surface treatment or not, and without silicon dioxide particle components were selected as comparative examples;

[0119] The preparation process is the same as that of Example 1;

[0120] The specific composition of the obtained anti-reflection optical film and the performance evaluation results are shown in Table 5.

[0121] Comparative Examples 5-7

[0122] Compared with Example 1, an anti-reflective coating prepared by using an anti-reflective coating solution without adding or adding a lower proportion of fluorine-modified oligomer is selected as a comparative example;

[0123] The preparation process is the same as that of Example 1;

[0124] The specific composition of the obtained anti-reflection optical film and the performance evaluation results are shown in Table 5.

[0125] Comparative Examples 8-12

[0126] Compared with Example 1, an anti-reflective coating prepared by using an anti-reflective coating solution of polyurethane-modified acrylate oligomers with different functionalities and different addition ratios was selected as a comparative example;

[0127] The preparation process is the same as that of Example 1;

[0128] The specific composition of the obtained anti-reflection optical film and the performance evaluation results are shown in Table 5.

[0129] Comparative Example 13

[0130] Compared with Example 1, an anti-reflection coating prepared by using an anti-reflection coating solution having trimethylolpropane triacrylate (TMPTA) added in different proportions was selected as a comparative example;

[0131] The preparation process is the same as that of Example 1;

[0132] The specific composition of the obtained anti-reflection optical film and the performance evaluation results are shown in Table 5.

[0133] Comparative Examples 14-15

[0134] Compared with Example 1, a hardened coating layer exposed to high-dose UV light and a hardened coating layer not subjected to plasma treatment were selected as comparative examples;

[0135] The preparation process is the same as that of Example 1;

[0136] The specific composition of the obtained anti-reflection optical film and the performance evaluation results are shown in Table 5.

[0137] The test method is as follows:

[0138] Transmittance and haze test: According to the standard "JISK7105-1981", i.e. "Test method for optical properties of plastics", the transmittance and haze of the hardened film in the visible light band are tested; the testing equipment is Nippon Denshoku NDH 7000;

[0139] Pencil hardness test: According to the "JISK5400-1990" standard, i.e. "Paint film adhesion test method", the pencil hardness of the hardened layer is tested using a Mitsubishi pencil test;

[0140] Adhesion test of hardened layer: According to GB 1720-1979, i.e., the method for testing adhesion of paint films, the adhesion between the hardened coating and the substrate is tested and recorded. 5B means that the coating has not fallen off, 4B to 1B respectively represent different degrees of coating falling off, and 0B means that the coating has completely fallen off.

[0141] Wear resistance test: According to the standard "HG / T 4303-2012", i.e. "Test method for wear resistance of surface hardened polyester film", the wear resistance of the hardened layer was tested using 0000# steel wool, 250gf / cm 2 The test equipment is Jinliang Industrial's wear tester A20-339. The wear resistance of the hardened film can be judged by testing the number of times the film surface is scratched.

[0142] Reflectivity test: The test was conducted in accordance with the ASTM F1252-2016 standard, i.e., Standard Test Method for Measurement of Optical Reflectivity of Transparent Materials. The test was completed using Konica Minolta's CM3600A. The non-test surface was covered with black tape (Bachuan).

[0143] Table 5 Coating liquids used in the examples and comparative examples and their anti-reflection optical film properties

[0144]

[0145] From the test results of the above embodiments and comparative examples, it can be concluded that the anti-reflection optical film of the present invention has a low reflectivity and can effectively suppress the reflection of ambient light; by introducing silica particles into the hardened coating and treating it with plasma, the adhesion between the hardened coating and the anti-reflection coating can be significantly improved; under the synergistic cooperation of the specific coating formula and the specific curing process of the hardened coating and the anti-reflection coating, the interlayer adhesion between the hardened coating and the anti-reflection coating is effectively improved. In short, the anti-reflection optical film of the present invention has a low reflectivity, while taking into account better wear resistance, hardness and durability, and can meet the durability requirements of long-term use.

[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An anti-reflection optical film, characterized in that: comprising a hard coating layer and an anti-reflection coating layer stacked on the hard coating layer; The hardened coating is formed by a hardening coating liquid, and the hardening coating liquid includes the following components: Difunctional polyurethane acrylate oligomer, hexafunctional polyurethane acrylate oligomer, photoinitiator, antistatic agent and silicon dioxide particles; The anti-reflective coating is formed by an anti-reflective coating liquid, and the anti-reflective coating liquid includes the following components: Difunctional polyurethane acrylate oligomer, tetrafunctional polyurethane acrylate oligomer, hexafunctional polyurethane acrylate oligomer, trimethylolpropane triacrylate, fluorine-modified resin, hollow silica microsphere dispersion, photoinitiator, antifouling agent and leveling agent.

2. The anti-reflection optical film according to claim 1, characterized in that: The hardened coating is laminated on the transparent substrate; Preferably, the transparent substrate comprises at least one of PET, SRF, TAC and PMMA; Preferably, the thickness of the transparent substrate is not less than 40 um; Preferably, the thickness of the hardened coating is 3um-4um; Preferably, the anti-reflection coating has a thickness of 100 nm-120 nm.

3. The anti-reflection optical film according to claim 1 or 2, characterized in that: The silicon dioxide particles include solid silicon dioxide particles; Preferably, the silica particles are random silica particles; Preferably, the particle size of the silica particles is 0.1um-0.2um; Preferably, the silica particles are silica particles with hydrophobic surface treatment.

4. The anti-reflection optical film according to claim 3, characterized in that: The antistatic agent includes an ionic antistatic agent; Preferably, the ionic antistatic agent is an anionic antistatic agent; Preferably, the anionic antistatic agent includes at least one of alkyl sulfonates, alkyl sulfates, alkyl phosphates and alkylphenol polyoxyethylene ether sulfates; Preferably, the anionic antistatic agent is bis(trifluoromethylsulfonyl)imide salt.

5. The anti-reflection optical film according to claim 1 or 2, characterized in that: The hollow silica microsphere dispersion includes at least one of a hollow silica microsphere dispersion treated with vinyl groups on the surface and a hollow silica microsphere dispersion treated with methacrylic acid groups on the surface; Preferably, the surface of the hollow silica microsphere has at least 2 vinyl reaction sites; Preferably, the particle size of the hollow silica microspheres is 30nm-100nm; Preferably, the wall thickness of the hollow silica microspheres is 5nm-6.5nm; Preferably, the porosity of the hollow silica microspheres is 40%-60%.

6. A method for preparing an anti-reflection optical film according to any one of claims 1 to 5, characterized in that: The following steps are involved: A hardening coating liquid is firstly coated on the surface of a transparent substrate and cured to form a hardened coating layer, and then an anti-reflection coating liquid is coated on the surface of the hardened coating layer and cured to form an anti-reflection coating layer, thereby obtaining the anti-reflection optical film.

7. The preparation method according to claim 6, characterized in that: The hardened coating layer is also subjected to a solvent volatilization step before curing; Preferably, the cumulative UV energy irradiated to the hardened coating during the curing process is 100 mJ / cm 2 -250mJ / cm 2 ; Preferably, the hard coating has unreacted active vinyl sites after curing.

8. The preparation method according to claim 6, characterized in that: The hard coating is further subjected to a plasma treatment step after being cured, so that the surfaces of the silicon dioxide particles floated onto the hard coating form active hydroxyl sites under the plasma treatment.

9. The preparation method according to claim 6, characterized in that: The anti-reflective coating is also subjected to a solvent volatilization step before curing; Preferably, the oxygen concentration of the anti-reflective coating during curing is less than 200 ppm, and the cumulative UV energy irradiated is 500 mJ / cm 2 -1000mJ / cm 2 .

10. Use of the anti-reflection optical film according to any one of claims 1 to 5 in a portable display device.

Citation Information

Patent Citations

  • Optical film and preparation method thereof

    CN115561843A